REDUCING RISK FACTORS IN THE WORKPLACE OF THE LASER SYSTEM OPERATOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Laser processing of materials takes an increasing place in production processes. Improving the performance, improving the quality of processing is not a complete list of the positive aspects of the introduction of laser processing, but there are a number of points that need to be paid attention to during the operation of laser systems - these are issues related to safety. The following risk factors are specific to laser systems: firstly, the laser beam itself, effects on the organs of vision, direct thermal effects on the skin and tissues, secondly, harmful products resulting from the interaction of the laser beam and the material being processed. Aerosols, smoke and dust have different effects on the human body, especially on the respiratory system and the publication considers the risks associated with the release of harmful products during laser processing and the existing methods for reducing the concentration of harmful substances in the working area with specific examples.